Piano Sonata no. 8 in C minor, op. 13 (Simrock) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Bonn; Germany; Simrock)
A new edition of the Piano Sonata no. 8 in C minor, op. 13, in upright format, using the same plate number as the earlier Simrock edition in oblong format published in 1800.